Why Secondary Towns Can Be Important for Poverty Reduction : A Migrant's Perspective - Ingelaere, Bert; Christiaensen, Luc; De Weerdt, Joachim; Kanbur, Ravi (World Bank, Washington, DC, 2017)
This paper develops the concept of "action space" as the range of possible destinations to which a migrant can realistically move at a given point in time and, intimately linked to this, the set of possible livelihoods at destination. It shows how this space expands and contracts over time through "cumulative causation." Such a dynamic framework allows for appreciating the role of secondary towns in rural-urban migration and poverty reduction. Secondary towns occupy a unique middle ground between semi-subsistence agriculture and the capitalistic city, between what is close by and familiar and what is much further away and unknown. By opening the horizons of the (poorer) rural population and facilitating navigation of the nonfarm economy, secondary towns allow a broader base of the poor population to become physically, economically, and socially mobile. Secondary towns therefore have great potential as vehicles for inclusive growth and poverty reduction in urbanizing developing countries. These are the insights emerging from the in-depth life history accounts of 75 purposively selected rural-urban migrants from rural Kagera, in Tanzania.